2021
DOI: 10.1039/d0bm01599g
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib loaded nanostructured lipid carriers for effective treatment of corneal neovascularization

Abstract: Corneal neovasularization (CNV) is one of the most important causes of visual impairment worldwide. Dasatinib, a poorly water-soluble tyrosine kinase inhibitor with dual Src family kinase and platelet derived growth...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…When developing ophthalmic drug delivery systems, eye safety has always been a major issue. Studies have shown that rabbits are more sensitive to eye irritants than humans; thus, the safety to human eyes can be estimated based on the results of animal experiments ((a) Li et al., 2021 ). Next, the Draize irritation test scoring standard was used to evaluate the irritation caused by SRB-NLC eye drops in rabbit eyes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When developing ophthalmic drug delivery systems, eye safety has always been a major issue. Studies have shown that rabbits are more sensitive to eye irritants than humans; thus, the safety to human eyes can be estimated based on the results of animal experiments ((a) Li et al., 2021 ). Next, the Draize irritation test scoring standard was used to evaluate the irritation caused by SRB-NLC eye drops in rabbit eyes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to drug selection, the drug delivery challenges for eye diseases should also be considered ((a) Li et al., 2021 ). Drug molecules that have a good effect in vitro may be ineffective in vivo due to inefficiency and insufficiency after topical administration.…”
Section: Introductionmentioning
confidence: 99%
“…The particle size of the shikonin-loaded MPEG-PCL micelles was in good accordance with that of the drug-loaded MPEG-PCL micelles reported previously. 30 Typically, micelle sizes is proportional to the block length. Drug-loaded nanoparticles with a relatively small size (20–200 nm) can accumulate in pathological regions such as sites of inflammation and tumors via enhanced permeability and retention effect.…”
Section: Discussionmentioning
confidence: 99%
“…The drug loading and encapsulation efficiency were calculated with the following equations: [30][31][32] Drug loading ð%Þ ¼ Amount of drug in micelles Total amount of micelles � 100…”
Section: Drug Loading and Encapsulation Efficiencymentioning
confidence: 99%
“… [ 305 ] NLC Glyceryl monostearate, lipoplysaccharides Dasatinib Observed sustained release, reduced ocular toxicity, and facilitated penetration into cornea via topical administration with effective inhibition of CNV. [ 306 ] Dendrimer Lecithin Anti-VEGF Plus Oligonucleotide 1 Topical delivery of dendrimers plus ODN-1 to the eyes of rats and inhibited laser-induced CNV for up to 6 months. [ 307 ] Niosomes DOTAP, squalene, Polysorbate 80 pDNA Persistent protein expression after transfection intravitreally for at least 1 month after injection.…”
Section: Formulation Approachesmentioning
confidence: 99%